Use of prescription opioid and other drugs among a cohort of persons with Ehlers–Danlos syndrome: A retrospective study. Issue 3 (9th January 2019) - Schubart, Jane R.; Schilling, Amber; Schaefer, Eric; Bascom, Rebecca; Francomano, Clair
Abstract : Against the backdrop of increased opioid prescribing in the United States and the associated high rate of side effects, dependence, and addiction, our study examined how opioids and other medications are being used among persons with Ehlers–Danlos syndrome (EDS). EDS is a set of heritable connective tissue disorders with high symptom burden, including chronic pain. Prescription medication use among persons with EDS was compared to a cohort of matched controls using 10 years of administrative claims data from a large database of privately insured patients (2005–2014). Our dataset included 4, 294 persons with EDS, ages 5–62 years old. In both adults and children, we found that the percentage of persons with a prescription drug claim was higher in the EDS cohort for all prescription drug classes examined. Among children, opioid use was double in the EDS cohort compared to the control group (27.5% vs. 13.5%); in adults, it was nearly double in EDS patients (62% vs. 34.1%). Among persons who were prescribed opioids, those with EDS had higher cumulative dosages over a 2‐year time period versus controls. Our study aids in understanding opioid and prescription drug use patterns in a vulnerable population with high symptom burden and chronic pain that is often severe.